Metabolic reprogramming in the tumor microenvironment: unleashing T cell stemness for enhanced cancer immunotherapy - Liu, Youhan; Wang, Tao; Ma, Wen; Jia, Zixuan; Wang, Qinglu; Zhang, Maoling; Luo, Ying; Sun, Hongmei (Frontiers in Pharmacology, 2023)
T cells play a pivotal role in the immune system by distinguishing between various harmful pathogens and cancerous cells within the human body and initiating an immune response. Within the tumor microenvironment (TME), immune effector T cells encounter both immunosuppressive cells and factors that hinder their functionality. Additionally, they endure robust and persistent antigenic stimulation, often leading to exhaustion and apoptosis. However, the stemness of T cells, characterized by their ability to survive and self-renew over extended periods, represents a primary target in immune checkpoint therapies such as anti-PD-1 therapy.T cell stemness encompasses specific memory T cell subsets and progenitor-exhausted T cells with stem cell-like properties. Therefore, understanding the impact of the TME on T cell stemness, including factors like K + , lactate, and H + , holds significant importance and can facilitate the mitigation of terminal T-cell depletion, the identification of potential resilient biomarkers or therapeutic targets resistant to immune checkpoint therapies, and ultimately lead to sustained anti-tumor effects. Thus, it offers a novel perspective for advancing tumor immunotherapy.